Evolution [videorecording (DVD)] : fossils, genes, and mousetraps. - Miller, Kenneth R. (Kenneth Raymond), 1948- (Howard Hughes Medical Institute, 2007)
Leading evolution educator Ken Miller discusses the controversy surrounding the teaching of evolution, presents compelling evidence for evolution and reasons why "intelligent design" is not scientific. The presentation features Dr. Miller's responses to questions from a live audience of high school students.